The Novel-Machine The Theory and Fiction of Anthony Trollope - Kendrick, Walter (Johns Hopkins University Press, 2019)
Originally published in 1980. The first section of The Novel-Machine consists of five short chapters that rewrite Autobiography as an undisguised theory of realistic fiction, exploring its paradoxes while placing it in the context of mid-Victorian criticism. Chapters 6 and 7 survey the manifestations in Trollope's novels of what his theory sets down as the primary difference of realism: its way of telling its readers how to read. Chapter 8 is a close reading of He Knew He Was Right, a neglected novel that, in Kendrick's estimation, deserves to stand in much higher critical esteem than it does. Kendrick shows how deeply woven into the texture of Trollope's writing the rhetoric of realism is. Kendrick's reading is a departure from the usual method of criticizing Trollope-surveying the whole of his work a novel at a time, saying a little about every novel and always too little about each.